Helicobacter pylori Affects the Antigen Presentation Activity of Macrophages Modulating the Expression of the Immune Receptor CD300E through miR-4270 - Pagliari, Matteo; Munari, Fabio; Toffoletto, Marta; Lonardi, Silvia; Chemello, Francesco; Codolo, Gaia; Millino, Caterina; Della Bella, Chiara; Pacchioni, Beniamina; Vermi, William; Fassan, Matteo; de Bernard, Marina; et al. (Frontiers in Immunology, 2017)
Helicobacter pylori (Hp) is a Gram-negative bacterium that infects the human gastric mucosa, leading to chronic inflammation. If not eradicated with antibiotic treatment, the bacterium persists in the human stomach for decades increasing the risk to develop chronic gastritis, gastroduodenal ulcer and gastric adenocarcinoma. The life-long persistence of Hp in the human stomach suggests that the host response fails to clear the infection. It has been recently shown that during Hp infection phagocytic cells promote high Hp loads rather than contributing to bacterial clearance. Within these cells Hp survives in “megasomes”, large structures arising from homotypic fusion of phagosomes, but the mechanism that Hp employs to avoid phagocytic killing is not completely understood. Here we show that Hp infection induces the down-regulation of specific miRNAs involved in the regulation of transcripts codifying for inflammatory proteins. miR-4270 targets the most up-regulated gene: the immune receptor CD300E, whose expression is strictly dependent on Hp infection. CD300E engagement enhances the pro-inflammatory potential of macrophages, but in parallel it affects their ability to express and expose MHC class II molecules on the plasma membrane, without altering phagocytosis. This effect compromises the possibility for effector T cells to recognize and activate the killing potential of macrophages, that, in turn would become a survival niche for the bacterium. Taken together, our data add another piece to the complicate puzzle represented by the long-life coexistence between Hp and the human host and contribute with new insights towards understanding the regulation and function of the immune receptor CD300E.